Reverse transcriptase polymerase chain reaction study to evaluate dissemination of cancer cells into circulation after incision biopsy in oral squamous cell carcinoma - Dyavanagoudar Sunita; Kale Alka; Bhat Kishore; Hallikerimath Seema (Wolters Kluwer Medknow Publications, 2008)
Background: Tissue manipulation by incisions, radiotherapy, and palpation may lead to dissemination of cancer cells into circulation. Circulating cancer cells in blood play a central role in metastatic process. Their numbers can be very small and for their detection,reverse transcriptase polymerase chain reaction (RT-PCR) has been successfully used in this study. Materials and Methods: To examine whether cancer cell dissemination results from incision biopsy, we tried to detect oral squamous cell carcinoma (OSCC) cells in the peripheral blood sample before and after incision biopsy by CK19 RT-PCR. The study group consisted of 25 OSCC patients and the control group consisted of five patients with oral submucos fibrosis and five with leukoplakia. Five ml of blood collected before and twice (15 and 30 min) after incision were used for CK19 RT-PCR. Results: Four (16%) of 25 cases of OSCC were positive for CK19 transcripts in their peripheral blood drained 15 min after incision. CK19 transcripts were not detected in the control group. Conclusion : Surgical invasion, in the form of incisional biopsy, causes dissemination of cancer cells into circulation, resulting in increased risk of metastasis.